PERBEDAAN EFEK TINGKAT PERLAKUAN ISTIMEWA YANG BERHUBUNGAN DENGAN PENDAPATAN: SEBUAH STUDI EMPIRIS PADA PELANGGAN TOKO SERBA ADA - Iwan Ekawanto; Robert Kristaung (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2015)
This study intends to empirically explore how the practices of loyalty programs conducted by the store management (department store) which benefit for customers so as to provide results that benefit both parties as a relational outcome consisting of relationship commitment, Increased purchases, share of customer, word of mouth and customer feedback, which is completed by respondents profile as control variables such as age, education and income levels. With sample 66respondents to test the hypothesis using MANOVA. Differential test results showed that there are differences in relationship commitment, increased purchases, share of customer, word of mouth, and customer feedback with a high level of preferential treatment, medium and low on the customer department store. Similarly, the age, income and education at the department store customersthere are differences there are differences in relationship commitment, Increased purchases, share of customer, word of mouth, and customer feedback. The results of testing the fifth hypothesis states that preferential treatment will give a high positive influence on relationship commitment, Increased purchases, share of customer, word of mouth, and customer feedback. The test result of five hypothesis states that high preferential treatment will give positive influence to the relationship commitment, increased purchases, and share of customer, word of mouth, and customer feedback. On relationship commitment is not significant covariates of age, but the share of customer revenue and customer feedback and education are not significant, whereas age has the effect of preferential treatment exhibited significantly coupled with the age factor share of the customer to customer.Similarly, the positive word of mouth, only the opinion of significant covariates as control variables of preferential treatment. These three covariates age, income and education only significant simultaneously at Increased purchase only.